EKSPLORASI ETNOMATEMATIKA TIMBANGAN IKAN : PENGUATAN KONSEP KONVERSI SATUAN BERAT ( KILOGRAM, KUINTAL, DAN TON ) UNTUK MELATIH PEMECAHAN MASALAH SISWA KELAS 6 SD - Trisnawati; Mu’jizatin Fadiana; Heny Sulistyaningrum (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Mathematics learning in elementary schools is often perceived by students as abstract and disconnected from everyday life. This condition results in low conceptual understanding and problem-solving skills, particularly in the topic of weight unit conversion. This article aims to examine the exploration of ethnomathematics in fish weighing activities as a meaningful learning context to strengthen the concept of weight unit conversion (kilograms, quintals, and tons) and train the problem-solving skills of sixth-grade elementary school students. The methods used are literature study and conceptual study of ethnomathematics practices in fish buying and selling activities in traditional markets and fishing ports. The results of the study indicate that fish weighing activities involving contextual weight units can connect mathematical concepts with students' real-life experiences, improve conceptual understanding, and train mathematical problemsolving skills. Thus, the integration of ethnomathematics with fish weighing has the potential to be an effective contextual learning approach for weight unit conversion material in elementary schools